2021
DOI: 10.1136/bmjgh-2021-007415
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported provision of person-centred maternity care among providers in Kenya and Ghana: scale validation and examination of associated factors

Abstract: IntroductionPerson-centred maternity care (PCMC), which refers to care that is respectful and responsive to women’s preferences needs, and values, is core to high-quality maternal and child health. Provider-reported PCMC provision is a potentially valid means of assessing the extent of PCMC and contributing factors. Our objectives are to assess the psychometric properties of a provider-reported PCMC scale, and to examine levels and factors associated with PCMC provision.MethodsWe used data from two cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 39 publications
(104 reference statements)
3
33
0
Order By: Relevance
“…56,57 The frequent exposure of maternity providers to adverse events necessitates the availability of mental health support that is accessible and responsive. Of note, only 13% of providers in our study reported ever participating in a stress management training, 27 while only a few providers reported physical exercise, meditation, taking deep breaths or other coping mechanisms. Providers need to be introduced to evidence-based coping mechanisms and dissuaded from adapting negative coping behaviors.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…56,57 The frequent exposure of maternity providers to adverse events necessitates the availability of mental health support that is accessible and responsive. Of note, only 13% of providers in our study reported ever participating in a stress management training, 27 while only a few providers reported physical exercise, meditation, taking deep breaths or other coping mechanisms. Providers need to be introduced to evidence-based coping mechanisms and dissuaded from adapting negative coping behaviors.…”
Section: Discussionmentioning
confidence: 64%
“…26,44,45 Concurrent with these findings, our quantitative findings have demonstrated that high stress and burnout are associated with low self-reported provision person-centred maternity care. 27 In our published quantitative analysis using validated psychosocial measures of stress, nearly all the providers (96%) had moderate to high levels of stress and more than 80% had some level of burnout, with 20% having high levels of burnout indicative of burnout of clinical concern. 20 Our findings, concurrent with previous findings, also underscore the longstanding dissatisfaction among health care providers which remains unresolved.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The data are from a cross-sectional study with healthcare providers who work in maternity units in the Upper East region (UER) of Ghana. The setting and data collection procedures have been previously described [47] and are brie y summarized here. A total of 150 Providers were recruited from 19 high volume delivery health facilities (an average of 75 births per month in the prior year) across the 15 districts in the region from October 2020 to January 2021.…”
Section: Design Participants Setting and Data Collectionmentioning
confidence: 99%